A Development of Assessment System for FSKTM Postgraduate Students - Nor Azim, Nor Amirul Akmal; Arbaiy, Nureize (Applied Information Technology And Computer Science, 2022)
Postgraduate programs by research are academic programs that require special assessment before a degree is given to students. At the Faculty of Computer Science and Information Technology, UTHM, the evaluation of research students is done at a certain time throughout the study. This assessment uses a printed form that will be distributed to panels and supervisors for the scoring process. The completed form will be returned to the graduate administration unit for analysis to obtain the final result. This process is repeated for all students undergoing assessment 1 and 2. Although this method is effective, with the advancement of digital technology and the addition of students, the process of implementing the collection of marks and calculation of the analysis of assessment results needs to be improved. Therefore, an assessment score management system for postgraduate programs has been proposed for its expansion to improve the efficiency of existing processes. This web-based system manages score entry and score analysis automatically. The system also handles information of students undergoing assessments 1 and 2 as well as the assessors involved. Prototype methodologies are used as project development guidelines, while project design is based on structured methods. Meanwhile, system development is realized using Sublime software and MySQL database. The programming languages ​​used are Hypertext Preprocessor (PHP) and Hypertext Mark-up Language (HTML). It is anticipated that this developed system can help streamline the process of evaluation, scoring and analysis.